Penerapan Metode Dijkstra untuk Menentukan Jalur Lintasan Terpendek Kota Kisaran Menuju Objek Wisata Simalungun - Zepri Pratama; Dedy Hartama; Muhammad Ridwan Lubis; Sundari Retno Andani; Ika Okta Kirana (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2020)
Kisaran City is one of the cities in North Sumatra Province, and Simalungun tourism object is a tourist destination located in Simalungun Regency, North Sumatra Province. The purpose of this paper is to determine the shortest path or alternative route from the town of Kisaran (the starting point) to one of the tourist objects in Simalungun which took 18 samples of tourist destinations. The method used in this proposed paper is the Djikstra method which is often used by researchers and academics to determine the shortest route or the fastest route on a journey (expedition). The research data used is only from the google map to calculate each route between cities to tourist objects in Simalungun district. The application used is a PHP web program to simulate the final display of the process of finding the shortest path. The results of this research are in the form of information so that the residents of Kisaran city will know better about the shortest and fastest route to get to tourist objects in Simalungun Regency.